INTEGRASI KEWIRAUSAHAAN MELALUI PENDIRIAN LEMBAGA PAUD SEBAGAI SALAH SATU PENGABDIAN KEPADA MASYARAKAT - Frinza, Frinza; Meidiana, Meidiana (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
In this all-creative era, we must be able to take advantage of all opportunities to become a source of livelihood if we cannot comply with the rules of other people's business work. Making PAUD Education as an entrepreneurial potential is not a new thing, but this field is not done by many people because other fields of business such as fashion and culinary look more promising. Even though the education sector can provide many benefits for both the manager, and for the local community. Children of PAUD age need to be educated from childhood because at this time the growth of the age of gold (gold ege) is increasing. Parents will provide the best education for children from an early age, especially in the midst of their busy work. Therefore PAUD entrepreneurs are currently mushrooming and even new players have emerged that are increasingly tightening competition. The challenge in entrepreneurial competition is how so that PAUD Institutions can continue to exist, survive, and improve, one of the factors that influences them is the management of learning. If the management is good, it will produce a good output that is producing children who are cheerful, cheerful, and balanced with IQ, EQ and SQ. PAUD units can be established by a) district / city government; b) village government; c) individuals; d) groups of people; e) legal entity.